2017
DOI: 10.1016/j.cej.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Removal of VOCs by catalytic process. A study of MnZnO composites synthesized from waste alkaline and Zn/C batteries

Abstract: Spent alkaline and zinc-carbon batteries were subjected to a biohydrometallurgy process, in order to recover manganese and mixed manganese zinc oxides. Two solids were synthesized, one of them prepared by reaction of MnSO4 and KMnO4 (MnOx) and the other obtained by chemical precipitation with NaOH (ZnMnO). The characterization by XRD, TPR, FTIR and XPS revealed the presence of Mn3+ and Mn4+ cations in both samples, and the presence of ZnO and Mn-Zn spinels in ZnMnO. The samples were evaluated in the oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For example, as unsupported K-doped manganese oxides catalyze the complete oxidation of ethanol to CO 2 at 430 K, alumina-supported catalysts with similar compositions allow full combustion at 473-500 K [46]. Poorly active catalysts indeed produce incomplete combustion with some acetaldehyde coproduction [47] by reaction (9), and due to the much higher toxicity of acetaldehyde with respect to ethanol, this needs to be completely avoided.…”
Section: Ethanol Total Oxidationmentioning
confidence: 99%
“…For example, as unsupported K-doped manganese oxides catalyze the complete oxidation of ethanol to CO 2 at 430 K, alumina-supported catalysts with similar compositions allow full combustion at 473-500 K [46]. Poorly active catalysts indeed produce incomplete combustion with some acetaldehyde coproduction [47] by reaction (9), and due to the much higher toxicity of acetaldehyde with respect to ethanol, this needs to be completely avoided.…”
Section: Ethanol Total Oxidationmentioning
confidence: 99%
“…The catalysts used are usually honeycombed structures with parallel channels coated with catalytic species (noble metals or metal oxides) by different methods such as sol–gel deposition, impregnation, or electrophoretic deposition . Many studies focused on the influence of the catalytic species to the removal of various VOCs such as toluene, , benzene, , formaldehyde, or ethanol . However, these types of fixed bed catalysts suffer from several drawbacks: (i) the cost of some catalytic species and coating and (ii) the diffusional limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Gallegos et al synthesized ZnMnO catalyst from the waste alkaline and Zn–C batteries via a biohydrometallurgy process, for the oxidation reaction of ethanol and toluene . The results showed that the MnOx and ZnMnO catalysts possessed the similar ethanol conversion, whereas the latter one possessed markedly higher toluene conversion, owing to a greater Mn/Zn ratio and the absence of a crystallized ZnO phase.…”
Section: Reutilization For Functional Materialsmentioning
confidence: 99%